2005
DOI: 10.1074/jbc.m410540200
|View full text |Cite
|
Sign up to set email alerts
|

Integrin α5/β1 Expression Mediates HER-2 Down-regulation in Colon Cancer Cells

Abstract: The inhibition of HER-2 signaling represents a potential mechanism by which integrin ␣5/␤1 exerts its tumor suppressor-like activity in colon cancer cells. These results also suggest that a novel function for integrin ␣5/␤1 is the control of HER-2 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 40 publications
0
38
1
Order By: Relevance
“…Increasing evidence suggests an interplay between HER-2 and integrins (19,20), a large family of cell surface heterodimeric receptors composed of α and β subunits (21). The β 1 subunit, which is encoded by the ITGB1 gene (also known as CD29 and VLAB), plays a major role in mediating cell-ECM interactions (22) and druginduced (23)(24)(25) or radiation-induced resistance (26), as well as in tumor initiation (27), progression, and invasion (22).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence suggests an interplay between HER-2 and integrins (19,20), a large family of cell surface heterodimeric receptors composed of α and β subunits (21). The β 1 subunit, which is encoded by the ITGB1 gene (also known as CD29 and VLAB), plays a major role in mediating cell-ECM interactions (22) and druginduced (23)(24)(25) or radiation-induced resistance (26), as well as in tumor initiation (27), progression, and invasion (22).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, increased expression of β 1 -integrin was associated with poor prognosis in patients with small-cell lung cancer (28), melanoma (29), and invasive breast cancer (30). Several arguments support the tenet that the deleterious effects of increased β 1 -integrin expression merit further investigation in the context of HER-2-positive breast cancer, notably, (a) binding of β 1 -integrin to ECM induces similar downstream signaling pathways to HER-2 (31), such as the PI3K/ Akt and extracellular signal-regulated kinase1/2 (ERK1/2) pathways (32); (b) reciprocal interactions (i.e., cross-talk) between HER-2 and integrins were reported in different cell types (19,20); (c) β 1 -integrin is overexpressed in JIMT-1 (33), a HER-2-positive breast cancer cell line isolated from a patient who did not respond to trastuzumab (34). Nonetheless, the prognostic relevance of β 1 -integrin expression in HER-2-positive breast cancer specimens and the functional consequences of its level of expression have not been investigated with respect to trastuzumab response.…”
Section: Introductionmentioning
confidence: 99%
“…Integrins on the cell surface were immunoprecipitated as described recently with slight modifications (16). Briefly, 5x10 5 cells were incubated with 9EG7 or TS2/16 antibodies at subsaturating concentrations (determined by flow cytometry) for 30 min at room temperature. After washing, cells were lysed with RIPA buffer containing protease inhibitors.…”
Section: Methodsmentioning
confidence: 99%
“…Changes in the expression of fibronectinbinding integrins have been detected in some transformed cells. For example, high levels of α5ß1 are inversely correlated to hepatocellular carcinoma malignancy (3) and tumorigenicity of CHO (4) and HT29 colon carcinoma cells (5,6). In contrast, gliomas display high levels of α5 subunits which are correlated with pathological malignancy (7).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that 1 1, 2 1, and 3 1 integrins regulate hepatocarcinoma cell invasion, angiogenesis of human squamous cell carcinoma, and increase migration and invasion of malignant glioma, melanoma and mammary adenocarcinoma cells, respectively. Expression of 5 1 integrin in colon cancer cells decreases HER-2-mediated proliferation (Kuwada et al, 2005). Loss of the 7 1 integrin in melanoma increases highly tumorigenic and metastatic phenotypes (Ziober et al, 1999).…”
Section: Surface Membrane Integrins As Potential Drug-discovery Targetsmentioning
confidence: 99%